Implementation of Good Corporate Governance and Digital Payment Systems in Islamic Banks to Support the Growth of MSMEs - Fadhilla Husna; Eli Febriani; Baginda Parsaulian (ICIEFS Proceeding, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a crucial sector in the Indonesian economy, contributing to job creation, increased income, and national economic growth. However, MSMEs still face challenges such as limited capital, financial literacy, and the use of digital technology. This study aims to examine the role of implementingGood Corporate Governance(GCG) in Islamic banking and the use of digital payment systems to support the improvement of MSME performance and growth. The research method used is a descriptive qualitative approach with a literature study, through analysis of various relevant literature related to the topic. The results of the study indicate that the application of GCG principles—transparency, accountability, responsibility, independence, and fairness—can increase MSME trust in Islamic banking while ensuring professional and sharia-oriented governance. On the other hand, the implementation of digital payment systems such as QRIS Sharia, mobile banking, and Islamic e-wallets has been proven to simplify transactions, increase efficiency, expand market access, strengthen financial transparency, and encourage Islamic financial inclusion. The synergy between GCG implementation and payment digitalization plays a crucial role in strengthening an inclusive and sustainable Islamic financial ecosystem, thereby increasing the competitiveness and growth of MSMEs in the digital era. Keywords: Good Corporate Governance, Digital Payment System, MSME Growth